Implementation of Independent Learning Curriculum in Elementary Schools - Ni, Laurentius; Leonangung Edu, Ambros; Santiana, Ingrida (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2025)
This research aims to: 1) Describe curriculum, curricular, co-curricular, and extra-curricular planning in implementing the independent learning curriculum at SDK Pagal I, Cibal District. (2) Describe the implementation of the curriculum, curricular, co-curricular, and extra-curricular in implementing the independent learning curriculum at SDK Pagal I, Cibal District. (3) Describe the evaluation of the curriculum, curricular, co-curricular, and extra-curricular in implementing the independent learning curriculum at SDK Pagal I, Cibal District. Through an in-depth case study approach, this research tries to delve into the depth of the issue using qualitative methods involving interviews, observation and documentation. The main respondents of this study were school principals and class I and IV teachers. 1) Independent curriculum planning at SDK Pagal I, Cibal District, has still not reached the maximum level. The main obstacle lies in the difficulty in planning co-curricular activities, where the teacher's lack of understanding and limited references are the main obstacles. 2) The implementation of the Independent Curriculum at SDK Pagal I has not reached the maximum level, especially in co-curricular activities. 3) Evaluation of the implementation of the Merdeka Curriculum at SDK Pagal I places more emphasis on aspects of the use of learning methods, use of learning media, availability of adequate facilities, and challenges in implementing co-curricular activities. Further efforts are needed to improve and enrich the implementation of the independent curriculum in these schools.